Draft Annual Plan 1987-88 Government of Gujarat - Planning Commission (Planning Commission, 1986)
The State experienced some difficulty in the generation and availability of power during the year on account of closure of some thermal units for short periods,, mainly for. maintenance and other technical reasons. The State also did not receive normal power from Korba power station on account of closure of some units. At the same time, there was greater demand of power for irrigation purpose because of inadequate rainfall. In view of the adequacy of power generation, the Government had to impose power cuts on H. T. consumers for some periods and to resort to load shedding to meet the energy requirement of various consumers as best as possible.
Government of Gujarat, General Administration Department (Planning)